Evaluación de cojinetes de deslizamiento basada en la norma ISO 7902:2020 // Evaluation of plain bearing performance according to standard ISO 7902:2020 - García Toll, Alejandra Elena; González Rey, Gonzalo; Carlos Deus Aguilera; de la Torre Silva, Francisco; Abreu Mesa, Osmel (Ingeniería Mecánica. Revista electrónica. ISSN 1815-5944, 2022)
La norma ISO 7902: Hydrodynamic plain journal bearing under steady-state conditions – Circular cylindrical bearings, es empleada ampliamente para la evaluación de cojinetes en diferentes condiciones de trabajo. En Cuba se ha usado el procedimiento propuesto por este documento, para evaluar cojinetes en diferentes condiciones de trabajo y sectores económicos, tanto por investigadores vinculados a la Universidad Tecnológica de La Habana, como en proyectos de otras universidades. El objetivo de esta investigación es evidenciar la actualidad y facilidad de aplicación de la norma ISO 7902. En el presente trabajo se expone el estudio de la tercera edición del procedimiento de cálculo de la norma del año 2020, para la simulación de un apoyo de un generador HSR7 637-8P de un motor Hyundai Himsen 9H 25/33 de una central eléctrica de fuel-oíl, obteniéndose resultados similares a las condiciones reales de operación. Se puede afirmar que se cuenta con una herramienta para prever los efectos que puedan ser provocados por acciones de control sobre el cojinete, modificación de las condiciones de trabajo y variaciones en el diseño. Palabras claves: norma ISO 7902; lubricación hidrodinámica; espesor de película de lubricante. _________________________________________________________________________________________________________________________________________________________ Abstract The international standard ISO 7902: Hydrodynamic plain journal bearing under steady-state conditions – Circular cylindrical bearings, is widely used for the evaluation of plain bearings in different operation conditions. In Cuba, the procedure proposed by this document has been used to evaluate plain bearings in different working conditions and productive sectors of the national economy, both by Universidad Tecnológica de La Habana researchers, and from other universities. The objective of this research is to demonstrate the relevance and feasibility of applying ISO 7902 standard. In this work research, a study of the load capacity calculation for plain bearings, according to the third edition of ISO standard 7902: 20202 is presented. The mentioned procedure was used to simulate the operating conditions and work capacity of a plain bearing support in an HSR7 637-8P generator of a Hyundai Himsen 9H 25/33 engine in a fuel-oil thermal power plant. The results show evidence of similarity between the simulation and the real operating conditions in the plain bearing. In this work, it could be concluded ISO standard 7902:2020 allows establishing a feasible procedure to apply to prevent the effects caused by control actions, working conditions and modification in the design of plain bearing. Key words: ISO 7902 standard; hydrodynamic lubrication, lubricant; film thickness.